2014
DOI: 10.12691/wjar-2-6-2
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Local and Introduced Varieties of <i>Pogostemon heyneanus</i> Benth. (Lamiaceae), for Superior Quality Physical, Chemical and Biological Parameters

Abstract: Pogostemon heyneanus Benth. (Lamiaceae) is an aromatic, perfumery important, industrial crop widely cultivated in many Asian countries for its distinguished fragrance and other therapeutic purposes. However, commercial cultivation of P. heyneanus was hampered due to lack of high quality planting materials. Purpose of the present study is to explore superior quality P. heyneanus variety by means of physical (morphological), chemical (physico-chemical, phytochemical, essential oil content and composition) and bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 21 publications
0
4
1
Order By: Relevance
“…The TFC of AE of D. triflorum whole plant and P. heyneanus leaves were 0.96±0.08 mg QE/g and 1.34±0.00 mg QE/g respectively. The TPC value of P. heyneanus leaves of the present study was lower than the reported data (0.83 ± 0.01 mg GAE/ g) 10 .…”
Section: B) Epidermal Cells and Crystals (C) Fibres (D) Trichomes (E)...contrasting
confidence: 96%
See 3 more Smart Citations
“…The TFC of AE of D. triflorum whole plant and P. heyneanus leaves were 0.96±0.08 mg QE/g and 1.34±0.00 mg QE/g respectively. The TPC value of P. heyneanus leaves of the present study was lower than the reported data (0.83 ± 0.01 mg GAE/ g) 10 .…”
Section: B) Epidermal Cells and Crystals (C) Fibres (D) Trichomes (E)...contrasting
confidence: 96%
“…Alkaloids and saponins were only observed in RAF. 10 . Moreover, the secondary metabolites observed in D. triflorum and P. heyneanus may be responsible for various pharmacological effects [32][33] .…”
Section: B) Epidermal Cells and Crystals (C) Fibres (D) Trichomes (E)...mentioning
confidence: 99%
See 2 more Smart Citations
“…The TLC plate was developed in the saturated chromatographic chamber containing different solvent systems 14 . Antibacterial Activity: The disc diffusion method was used to test antimicrobial activity against 3 bacterial species.…”
Section: Plant Extracts Preparationmentioning
confidence: 99%